2023
DOI: 10.1021/jacs.3c01088
|View full text |Cite
|
Sign up to set email alerts
|

Helical Bilayer Nanographenes: Impact of the Helicene Length on the Structural, Electrochemical, Photophysical, and Chiroptical Properties

Abstract: Helical bilayer nanographenes (HBNGs) are chiral πextended aromatic compounds consisting of two π−π stacked hexabenzocoronenes (HBCs) joined by a helicene, thus resembling van der Waals layered 2D materials. Herein, we compare [9]HBNG, [10]HBNG, and [11]HBNG helical bilayers endowed with [9], [10], and [11]helicenes embedded in their structure, respectively. Interestingly, the helicene length defines the overlapping degree between the two HBCs (number of benzene rings involved in π−π interactions between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 94 publications
2
24
0
Order By: Relevance
“…Density functional theory (DFT) calculations at the B3LYP-D3­(BJ)/6-31G­(d) level were performed to gain a deeper insight into the electronic structures of NGs 1 – 3 . It is found that both the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) are localized on the bridged half side of 1 – 3 rather than the entire conjugated backbone, similar to other reported bilayer and trilayer NGs. , Elongating the molecular backbone from 1 to 3 causes a gradual increase in the HOMO energy level and a decrease in the LUMO energy level, leading to narrower energy gaps for 2 and 3 , which closely matched the experiment results. Based on the results of time-dependent (TD)-DFT calculations, the maximum absorption peaks (λ max ) of 1 (calculated value of 524 nm), 2 (calculated value of 559 nm), and 3 (calculated value of 579 nm) can be assigned to the HOMO → LUMO transition, which concurs with the peak values obtained from experimental measurements (Figure c and Tables S4–S6).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Density functional theory (DFT) calculations at the B3LYP-D3­(BJ)/6-31G­(d) level were performed to gain a deeper insight into the electronic structures of NGs 1 – 3 . It is found that both the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) are localized on the bridged half side of 1 – 3 rather than the entire conjugated backbone, similar to other reported bilayer and trilayer NGs. , Elongating the molecular backbone from 1 to 3 causes a gradual increase in the HOMO energy level and a decrease in the LUMO energy level, leading to narrower energy gaps for 2 and 3 , which closely matched the experiment results. Based on the results of time-dependent (TD)-DFT calculations, the maximum absorption peaks (λ max ) of 1 (calculated value of 524 nm), 2 (calculated value of 559 nm), and 3 (calculated value of 579 nm) can be assigned to the HOMO → LUMO transition, which concurs with the peak values obtained from experimental measurements (Figure c and Tables S4–S6).…”
Section: Resultssupporting
confidence: 87%
“…Alternatively, electron diffraction (ED) that has been proven superior to dealing with the tiny crystals , was applied and successfully resolved the single-crystal structure of NG 3 , revealing its clear tetralayer structure with four HBC subunits linked by three [7]­helicene units with the interlayer distances of 3.56, 3.67, and 4.20 nm, respectively (Figure e, CCDC no. 2289385), comparable with the reported bilayer and trilayer NGs. , In addition, NG 1 crystallized in the P 1̅ space group with obvious intermolecular π–π stacking between P and M isomers (π–π distance: 3.70 Å) (Figure b). For NGs 2 and 3 , the homochiral isomers are arranged along the a -axis and c -axis, respectively, without π–π interaction due to the blocked stacking between π faces caused by the surrounding tert -butyl groups (Figure d,f).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The situation is common among [6]helicenes or smaller analogues 14,37,38,44,45,48,50,51,77 and may be tackled by different structural designs, such as double-helicenes, S-shaped or 8-shaped helical conjugated systems, elongated or extended helicenes. 46,77–84 Interestingly enough, in several of the just mentioned reports, the molecular design was steered by a preliminary computational screening, which confirms the demand for accurate computational approaches for property predictions.…”
Section: Resultsmentioning
confidence: 76%